A history of women in America - Coryell, Janet L. 1955-; Faires, Nora Helen (McGraw-Hill, 2012)
A History of Women in America integrates the stories of women in America into the national narrative of American history. By weaving women's lives into the heart of the country's narratives, readers will see women where they were, rather than having them appear as appendages to events controlled largely by men. Coryell and Faires use accessible language, telling stories that will attract beginning scholars to the field of history. Major ethnic groups are incorporated, from Native American and African women who appear earliest in the text, to the major immigrant groups, such as Hispanic, Latina, Chicana, and Asian women, who occupy increasingly larger roles throughout the nineteenth and twentieth centuries.